The Correlation Between Students’ Learning Environment and Their Critical Thinking Skill Development - Adalta, Febri Aini; Sujarwati, Iis (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2023)
This research aims to determine if there is a correlation between learning environment and students' critical thinking skill development. Research method that is used is Correlation. The sample in this research is 25 university students of the English Education Department. Instruments used in this research were questionnaires and practice tests. The questionnaire sheet adapted from The Dundee Ready Education Environment Measure (DREEM). it is used to find out students' opinions about their learning environment. Other instrument that is used is the practice test of Critical Thinking Appraisal which was used to determine the level of students’ critical thinking ability. In analyzing the data, this research used the product-moment correlation analysis technique. The results shows that there are no correlations between learning environment and the development of students’ critical thinking skills. Building a good learning environment is important and can support a good learning process.